Experimentally Shock‐Induced Melt Veins in Basalt: Improving the Shock Classification of Eucrites - Haruka Ono; Kosuke Kurosawa; Takafumi Niihara; Takashi Mikouchi; Naotaka Tomioka; Junko Isa; Hiroyuki Kagi; Takuya Matsuzaki; Hiroshi Sakuma; Hidenori Genda; Tatsuhiro Sakaiya; Tadashi Kondo; et al. (Geophysical Research Letters, 2023)
Abstract Basaltic rocks occur widely on the terrestrial planets and differentiated asteroids, including the asteroid 4 Vesta. We conducted a shock recovery experiment with decaying compressive pulses on a terrestrial basalt at the Chiba Institute of Technology, Japan. The sample recorded a range of pressures, and shock physics modeling was conducted to add a pressure scale to the observed shock features. The shocked sample was examined by optical and electron microscopy, electron back‐scattered diffractometry, and Raman spectroscopy. We found that localized melting occurs at a lower pressure (∼10 GPa) than previously thought (>20 GPa). The shocked basalt near the epicenter represents “shock degree C” of a recently proposed classification scheme for basaltic eucrites and, as such, our results provide a pressure scale for the classification scheme. Finally, we estimated the total fraction of the basaltic eucrites classified as shock degree C to be ∼15% by assuming the impact velocity distribution onto Vesta.